Post-Conflict Political Dynamics In Poso: Examining Neopatrimonial Practices 2005-2024 - Ahmad Hasan Ubaid; Mahira Sandria Rahmatiana; Gertha Maria Gultom; Taufik Akbar (LPPM Universitas PGRI Sumatera Barat, 2023)
This study investigates how post-conflict governance in Poso has been shaped by neopatrimonial practices and how hybrid political orders endure despite the formalization of peace agreements. The research aims to explain the persistence of elite domination in the region by examining the ways in which local actors consolidate their power through control of resources, patronage networks, clientelism, and the mobilization of religious sentiment. To achieve this, the study employs a qualitative explanatory approach, relying on in-depth interviews with key informants, analysis of official documents, electoral results, and secondary materials such as books, journals, and online publications. The findings reveal that while the Malino Declaration of 2001 was successful in reducing the intensity of violent conflict between Christian and Muslim communities, it fell short of producing a more inclusive and democratic political order. Instead, the political arena in Poso remains dominated by a small circle of elites who sustain the status quo and use both formal and informal mechanisms to secure their authority. These dynamics demonstrate that neopatrimonialism continues to influence the post-conflict political landscape, giving rise to a hybrid political order in which democratic institutions formally exist but function in parallel with clientelistic practices and elite-driven governance. The study concludes that without addressing the entrenched neopatrimonial system, post-conflict democratization in Poso will remain limited, and power will continue to circulate within narrow elite networks rather than being shared more broadly across society.